Information systems : research, development, applications, education : 11th SIGSAND/PLAIS EuroSymposium 2018, Gdansk, Poland, September 20, 2018, Proceedings /: research, development, applications, education : 11th SIGSAND/PLAIS EuroSymposium 2018, Gdansk, Poland, September 20, 2018, Proceedings. (2018) - Unknown
No abstract available